Organizational Culture as a Driver of Employee Engagement: A Systematic Review - Nursalimah, Siti; Rachman, Ghea Ivana Kusuma; Andriyani, Andriyani; Darmastuti, Ismi (Economic and Business Horizon, 2025)
This study aims to explore the role of organizational culture as a driver of employee engagement through a systematic review of relevant literature. Inclusive and adaptive organizational cultures have been shown to have a positive impact on employee engagement levels, contributing to improved performance and productivity within organizations. This research identifies the most influential cultural elements, such as shared values, open communication, and inclusive leadership, which significantly enhance employee motivation and engagement in day-to-day tasks. The method used is a systematic literature review based on the PRISMA guidelines to ensure a transparent process of study identification, screening, and selection. The review results show that organizational culture affects employee engagement across various types of organizations and industries, with an inclusive work environment playing a crucial role in driving employee engagement. However, gaps remain in the research on the application of organizational culture in more dynamic sectors and contexts, such as flexible and remote work environments. This study provides both academic and practical contributions for organizations to create a culture that better supports employee engagement, aiming for more optimal shared goals.